2014
DOI: 10.1002/ijc.29079
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the relaxin hormonal pathway in prostate cancer

Abstract: Targeting the androgen signalling pathway has long been the hallmark of anti-hormonal therapy for prostate cancer. However, development of androgen-independent prostate cancer is an inevitable outcome to therapies targeting this pathway, in part, owing to the shift from cancer dependence on androgen signalling for growth in favor of augmentation of other cellular pathways that provide proliferation-, survival-and angiogenesis-promoting signals. This review focuses on the role of the hormone relaxin in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 151 publications
(311 reference statements)
0
14
0
Order By: Relevance
“…Exogenous Wnt3a is routinely added to stimulate the Here, we tested the hypothesis that the effects of RLX on Nav1.5 and fibrosis are mediated by canonical Wnt signaling. While RLX and Wnt signaling have been investigated in models of cancer[184][185][186], there is no work on the interactions of the RLX and Wnt pathways in adult heart and 'healthy' aging as a precursor of cardiac diseases. We focused on hearts from 9-month (adult) and 24-month-old (aged) Fischer 344/Brown Norway F1 (F-344) male rats obtained from the National Institute of Aging.…”
mentioning
confidence: 99%
“…Exogenous Wnt3a is routinely added to stimulate the Here, we tested the hypothesis that the effects of RLX on Nav1.5 and fibrosis are mediated by canonical Wnt signaling. While RLX and Wnt signaling have been investigated in models of cancer[184][185][186], there is no work on the interactions of the RLX and Wnt pathways in adult heart and 'healthy' aging as a precursor of cardiac diseases. We focused on hearts from 9-month (adult) and 24-month-old (aged) Fischer 344/Brown Norway F1 (F-344) male rats obtained from the National Institute of Aging.…”
mentioning
confidence: 99%
“…All three known target genes, KCNH2, ADRB1 and ADRB2, were included in this subnetwork. Meanwhile, this subnetwork also captured 12 disease- Relaxin signaling pathway, AGE-RAGE signaling pathway and prostate cancer have also been widely investigated and reported in the previous works (Bao, et al, 2015;Neschadim, et al, 2015;Ozvegy-Laczka, et al, 2005). Moreover, autophagy and focal adhesion were two widely observed biological processes in cancer (Eke and Cordes, 2015;Farrow, et al, 2014).…”
Section: Excellent Performance and General Applicability Of Kddanet Cmentioning
confidence: 84%
“…Several proteoglycans have been proven to promote tumor progression and metastasis in ccRCC [32,33] . Previous reports have indicated that relaxin could affect cell growth, cell migration, angiogenesis and extracellular matrix remodeling, targeting Relaxin signaling pathway has gradually become a promising therapeutic way in cancer treatment [34,35] . Axon guidance is integral to several basic cellular processes, including organogenesis, regeneration, wound healing.…”
Section: Discussionmentioning
confidence: 99%